VALIDASI TINGKAT TERATOGENISITAS EKSTRAK ETANOL AKAR QUSTHUL HINDI (Saussurea costus) PADA MENCIT BETINA - Salsabila Marfyanda; Sri Indah Lestari; Ulfi Fadilah (LPPM Universitas Abdurrab, 2022)
Use medicine that comes from from materials chemical cause worries for mother pregnant so that more choose for consuming herbal medicine, one of them root Qusthul Hindi. Qusthul Hindi (Saussurea costus) is herbal plant origin from India as well have benefit as anticancer, antimicrobial and antiinflammatory. Though trusted herbal medicine have effect small side, will but materials chemical contained can also affect condition fetus, so need teratogenic test done with destination for knowing effect teratogenic root Qusthul Hindi (Saussurea costus) on growth and development fetus. Study this use root Qusthul Hindi (Saussurea costus) doses of 500 mg/kg BB and 1500 mg/kg BB and control given every day orally to mice female pregnant (Mus musculus) during 6-15 days of pregnancy. Then mice dissected on the 18th day of gestation and the fetus obtained observed one one by one for see existence effect teratogenic in the form of defects, abnormal number and shape. From result study extract ethanol root Qusthul Hindi (Saussurea costus) on control no experience effect teratogenic. At a dose of 500 mg/kg BB body weigh experience death and not found effect teratogenic. At a dose of 1500 mg/kg body BB no found effect teratogenic to the fetus, but whole fetus experience miscarriage (abortivum).